Regarding Coinfection With Denge Viruses and Agents of Hemocontact Infections in the Socialist Republic of Vietnam - Yu. V. Ostankova; E. V. Naidenova; E. N. Serikova; A. N. Schemelev; D. E. Valutite; E. B. Zueva; Hoang Khanh Thu Huinh; A. V. Semenov (Проблемы особо опасных инфекций, 2021)
According to the WHO, there is an increase in the number of cases of dengue fever worldwide. In many countries, where dengue fever is an endemic disease, blood-borne infections associated with hepatitis B and C viruses and HIV are widespread. The Socialist Republic of Vietnam is an endemic region for these pathogens. The unique epidemiological situation in the country provides an excellent opportunity to study the interaction between Arboviruses, agents of parenteral viral hepatitis B and C, and HIV infection in the body of sick people.The aim of this review was to analyze the literature data on the detection of cases of simultaneous infection with Dengue viruses of 1–4 types and agents of blood-borne infections in sick people in the Socialist Republic of Vietnam. Despite the fact that the simultaneous circulation of these pathogens in the patient's body can affect the pathophysiological mechanisms of the disease development, there were very few works devoted to co-infection with Dengue viruses and HIV, hepatitis C or B viruses, including in the regions adjacent to Vietnam. Therefore, research in this direction is promising for both fundamental science and practical medicine.